2018
DOI: 10.1021/acs.jpclett.7b03232
|View full text |Cite
|
Sign up to set email alerts
|

Well-Ordered 4CzIPN ((4s,6s)-2,4,5,6-Tetra(9-H-carbazol-9-yl)isophthalonitrile) Layers: Molecular Orientation, Electronic Structure, and Angular Distribution of Photoluminescence

Abstract: We fabricated a well-ordered homogeneous monolayer of disk-shaped, carbazolyl dicyanobenzene (CDCB)-based thermally activated delayed fluorescence (TADF) molecule, i.e., 4CzIPN((4s,6s)-2,4,5,6-tetra(9Hcarbazol-9-yl)isophthalonitrile) at room temperature on flat Ag(111), Au(111), and Cu(111) surfaces. The second layer of the 4CzIPN was also found to be well ordered. The electronic states of the well-ordered monolayer and multilayer of 4CzIPN were found to be nearly unchanged from that of the isolated molecule c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 16 publications
(34 reference statements)
1
34
0
Order By: Relevance
“…TADF compounds thus typically possess emissive charge-transfer (CT) states and the direction of their TDM often coincides with (or is very close to) the long molecular axis between donor and acceptor units. Note that there are some exceptions like the well-known 4CzIPN, which is an almost spherical molecule (Hasegawa et al, 2018 ). Nevertheless, the inline alignment of TDM and long molecular axis of TADF emitters holds great potential for manipulating their TDM orientation, and thus the light outcoupling from the OLED, by controlling molecular orientation upon thermal evaporation of films.…”
Section: Basic Approachmentioning
confidence: 99%
“…TADF compounds thus typically possess emissive charge-transfer (CT) states and the direction of their TDM often coincides with (or is very close to) the long molecular axis between donor and acceptor units. Note that there are some exceptions like the well-known 4CzIPN, which is an almost spherical molecule (Hasegawa et al, 2018 ). Nevertheless, the inline alignment of TDM and long molecular axis of TADF emitters holds great potential for manipulating their TDM orientation, and thus the light outcoupling from the OLED, by controlling molecular orientation upon thermal evaporation of films.…”
Section: Basic Approachmentioning
confidence: 99%
“…For example, it has been reported that several linear shaped rod-like and planar disk-shaped TADF emitters can achieve an V H as high as 97 % without considering other fabricationrelated parameters. [67] In practice, as discussed earlier for the conventional fluorescent materials, the intermolecular interactions play a determining role in providing a high degree of internal rigidity, which induces the high aspect ratios typically observed in molecules forming highly oriented films. Liu et al [66] Recently, another molecular design strategy has been focused on engineering intermolecular interactions.…”
Section: Effects Of Molecular Structurementioning
confidence: 98%
“…Unlike the IQE, there is relatively limited literature specifically investigating the molecular orientation effects in TADF emitters. [63,[65][66][67][68]73] Indeed, as discussed earlier, the overall planarity and geometrical shape of the molecule plays crucial roles. For example, it has been reported that several linear shaped rod-like and planar disk-shaped TADF emitters can achieve an V H as high as 97 % without considering other fabricationrelated parameters.…”
Section: Effects Of Molecular Structurementioning
confidence: 99%
See 1 more Smart Citation
“…TADF compounds thus typically possess emissive charge-transfer (CT) states and the direction of their TDM often coincides with (or is very close to) the long molecular axis between donor and acceptor units. Note that there are some exceptions like the well-known 4CzIPN, which is an almost spherical molecule (Hasegawa et al, 2018). Nevertheless, the inline alignment of TDM and long molecular axis of TADF emitters holds great potential for manipulating their TDM orientation, and thus the light outcoupling from the OLED, by controlling molecular orientation upon thermal evaporation of films.…”
Section: Basic Approachmentioning
confidence: 99%